Peran Guru Pendidikan Jasmani dan Olahraga dalam Membina Karakter Siswa Madrasah Ibtidaiyah Swasta Nurun Najah Kota Jambi - Abdillah Fahlevi; Donal Saputra (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to analyze the role of Physical Education and Sports (PJOK) teachers in fostering the disciplined character of fifth-grade students at the Nurun Najah Private Elementary Madrasah in Jambi City. Discipline is an important character value that needs to be instilled early on, and PJOK teachers have a strategic role in instilling it through physical activities, games, and rules in learning. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The subjects of the study included PJOK teachers, fifth-grade students, and the head of the madrasah. The results showed that PJOK teachers act as models, mentors, and evaluators in fostering student discipline through the application of rules, giving examples, and positive and negative reinforcement. Supporting factors include school support and student enthusiasm, while constraints include limited facilities and differences in student backgrounds. The implications of this study emphasize the importance of collaboration between teachers, parents, and schools in strengthening the formation of students' disciplined character.